Ciganos nas terras do Espírito Santo: representações sócio-políticas (1870-1936) - Durante, Daniela Simiqueli (2014)
The dissertation was developed in PPGHIS/UFES field is about brasilian gipsies population and it has as one"s objective to carry out a historiography study, using a time space between 1870 to 1936 ages in the Espírito Santo state. This investigation based on Roger Chartier theory.The Social representation argued author aim that there is a constant search to legitimize a social identity where, many time, it occurs other social groups despise.Social reality comprehension especific transports to remove the blindfold from this contexto, through social actors analysis.Reference period gipsies study was possible trough age society comprehension, examining periodical speech, gipsy action and what he represented for dominant group.For this purpose, Espírito Santo state journals were researched in this fixed period.Them, many gipsies representation were proved in studied age society where their apropriation significant contributed to invisible etnic minority in state.